TAVR in the tricuspid domain: valve-in-valve transcatheter tricuspid valve replacement for bioprosthetic valve degeneration. Issue 9 (29th September 2022) - Budweg, Jeffery; Joseph, Ryan; Perry, Christopher; Shah, Khanjan; Choi, Calvin; Jeng, Eric
Abstract : We report a novel use of transcatheter aortic valve replacement (TAVR) for valve-in-valve tricuspid valve replacement. A man in his 50s with prohibitive risks for surgical intervention underwent this procedure to improve severe, symptomatic tricuspid stenosis. Though current literature is limited to case reports, the Valve-in-Valve International Database (VIVID) reports similar mortality rates between surgical and transcutaneous replacement. As a novel, off-label procedure, there is limited operator experience. Nonetheless, in non-operative or high-risk patients, similar outcomes are noted in between transcatheter tricuspid valve replacement and surgical replacement. This registry sets the framework for further studies with the possibility of observing outcomes as operator experience increases, while highlighting the feasibility of the procedure.